Can a psychological-educational supportive intervention enhance the psychological well-being and academic performance of freshman medical students? - Mahdi Ebrahimi; Hamideh Baakhlagh; Emad Ebrahimzadeh; Bita Najjari; Maryam Amirkalali; Sara Raji; Amirhosein Ziaee; Alireza Omranzadeh; Sindokht Norouz; Hanieh Abedi; Zahra Rajai (Mashhad University of Medical Sciences, 2021)
Background: Freshman medical students experience high levels of distress, which may affect their learning ability. The present study assessed the effectiveness of a psychological-educational supportive package on the psychological well-being and the academic performance of freshman medical students.Methods: We included all the first-year medical students of Mashhad University of Medical Sciences in the educational year of 2018-2019 in the present study, using the census method.  The first-year medical students of autumn semester 2018 formed the control group and those in winter semester 2019 formed intervention group. 102 students among the control and 129 students (divided into 13 groups) among the intervention group voluntarily completed the study. The intervention was a psychological-educational supportive package designed to provide a supportive environment for freshmen and enhance peer-group interactions, increase emotional intelligence, coping and problem-solving strategies. It consisted of 6 weekly group sessions for first-year medical students, followed by follow-up sessions until the end of the first semester. The outcome measures were Grade Point Average (GPA) of the first and second semesters as the indicators of academic performance and the General Health Questionnaire-28 (GHQ-28) at the beginning of the first semester, at the end of the semesters to quantify the level of psychological well-being.Results: The mean GHQ-28 changes in the intervention group were significantly higher than the control group (pre-test/post-test: P= 0.013, post-test/follow-up: p <0.0001). In the intervention group, GPA was significantly higher than the control group in both the first and second semesters (P=0.016, p <0.0001, respectively).Conclusion: Psychological-educational intervention improved the level of psychological well-being and academic performance of freshman medical students.